2004
DOI: 10.1039/b313921b
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and evaluation of highly active imidotitanium ethylene polymerisation catalysts using high throughput catalyst screening

Abstract: A family of ca. 50 imidotitanium precatalysts [Ti(NR)(Me(3)[9]aneN(3))Cl(2)](R = alkyl or aryl; Me(3)[9]aneN(3)= 1,4,7-trimethyltriazacyclononane) were prepared in good yields using semi-automated procedures; high-throughput screening techniques identified seven highly active ethylene polymerisation precatalysts with activities in the range ca. 3 400 to 10 000 kg(PE) mol(-1) h(-1) bar(-1).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
84
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(86 citation statements)
references
References 20 publications
2
84
0
Order By: Relevance
“…Adams et al reported on the discovery of new imidotitanium catalysts for the polymerization of ethylene. [309] The catalysts were prepared by semi-automated parallel syntheses from 50 commercially available amines. While details on the polymers and catalysts are given, no details on the highthroughput polymerization screening methods used are provided.…”
Section: Polymerization Catalysts For Polyolefinsmentioning
confidence: 99%
“…Adams et al reported on the discovery of new imidotitanium catalysts for the polymerization of ethylene. [309] The catalysts were prepared by semi-automated parallel syntheses from 50 commercially available amines. While details on the polymers and catalysts are given, no details on the highthroughput polymerization screening methods used are provided.…”
Section: Polymerization Catalysts For Polyolefinsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Both computational and experimental studies have been performed to probe the structure and reactivity of these systems. It has been shown that Group 4 transition-metal imides have potential in CÀH activation chemistry, [8][9][10][11][12][13][14][15][16] materials chemistry [17][18][19][20] and olefin polymerisation catalysis (with the imide acting as an "ancillary ligand"), [21][22][23] and that these systems can be utilised in an wide variety of stoichiometric and sometimes catalytic coupling reactions with unsaturated substrates. [6] Terminal titanium imido complexes were first structurally characterised in 1990, [24,25] and since then a large number of imido complexes with different ancillary ligands have been synthesised.…”
Section: Introductionmentioning
confidence: 99%
“…[50][51][52] In particular, high-throughput methods have recently been used to discover a range of olefin polymerisation catalysts. [53][54][55][56][57] While these methods have been used in the evaluation of lanthanide catalysts, 58 their use has not flourished in contrast to their utility in organotransition metal chemistry. This may be due to the perception that lanthanide based catalysts are less robust and more reactive than their transition metal counterparts.…”
Section: Introductionmentioning
confidence: 99%